Fission Yeast Dna2 Is Required for Generation of the Telomeric Single-Strand Overhang - Tomita, Kazunori (American Society for Microbiology, 2004)
It has been suggested that the Schizosaccharomyces pombe Rad50 (Rad50-Rad32-Nbs1) complex is required for the resection of the C-rich strand at telomere ends in taz1-d cells. However, the nuclease-deficient Rad32-D25A mutant can still resect the C-rich strand, suggesting the existence of a nuclease that resects the C-rich strand. Here, we demonstrate that a taz1-d dna2-2C double mutant lost the G-rich overhang at a semipermissive temperature. The amount of G-rich overhang in S phase in the dna2-C2 mutant was lower than that in wild-type cells at the semipermissive temperature. Dna2 bound to telomere DNA in a chromatin immunoprecipitation assay. Moreover, telomere length decreased with each generation after shift of the dna2-2C mutant to the semipermissive temperature. These results suggest that Dna2 is involved in the generation of G-rich overhangs in both wild-type cells and taz1-d cells. The dna2-C2 mutant was not gamma ray sensitive at the semipermissive temperature, suggesting that the ability to process double-strand break (DSB) ends was not affected in the dna2-C2 mutant. Our results reveal that DSB ends and telomere ends are processed by different mechanisms.